Diffuse pollution characteristics of respirable dust in fully-mechanized mining face under various velocities based on CFD investigation. (20th May 2018) - Zhang, Qi; Zhou, Gang; Qian, Xinming; Yuan, Mengqi; Sun, Yanlong; Wang, Dan
Abstract: In order to grasp the partition diffusion and pollution of respirable dust under various turbulent velocities in fully-mechanized mining face, Finite Volume Method was adopted to simulate and study the diffusion behavior characteristics of respirable dust of 52305-1 fully-mechanized mining face in Daliuta coal mine at different areas under full section independent negative pressure ventilation conditions based on airflow streamline, airflow vector, and dust trace. Especially the dust particle movements under the impact of turbulent inlet velocity were defined accurately. The results show that a narrow and long high-speed zone is formed between the coal shearer and corresponding hydraulic pillars due to the blocking effect of coal shearer. At the height of breathing zone, the area with maximum air velocity is performed from the variable cross section, the maximum velocity reaches up to 1.44–2.52 times over inlet air velocity, also the value decreases as the inlet air velocity increases. Average respirable dust concentration of breathing zone height decreases with the increase of inlet air velocity, however the decreasing degree is weakened gradually. With the increase of turbulent inlet velocity, the settlement range of the dust from advancing support and the transverse diffusion range of the dust from drum cutting coal is gradually reduced, also the high concentration respirable dust area with more than 1440 mg/m 3 gradually disappear. When the inlet air velocity is over 2.5 m/s, the effect of dust removal by ventilation is weakened gradually. Highlights: Full scale refined partition physical model with original proportion. Parameters setting based on field measurement with more precise apparatus. Partition pollution of respirable dust from different dust sources is studied. The pollution mechanism of respirable dust under different velocity is obtained. The maximal allowable turbulent velocity for dust removal is investigated.